Local Government Strategies for Responding to Sexual Violence against Children in West Kalimantan - Meilinda, Selvi Diana (Universitas Islam Negeri Raden Intan Lampung, 2025)
Child sexual violence remains one of the most underreported and complex forms of gender-based harm, shaped by power asymmetry, structural vulnerability, and uneven institutional capacity at the local government level. This study examines the extent to which local governments in West Kalimantan operationalize the three pillars of response (prevention, intervention, and rehabilitation) by analysing 2024 -2025 case records, subnational regulatory frameworks, and institutional practices of DP3A, UPTD PPA, P2TP2A, and KPAD. Findings indicate a fragmented governance landscape in which provincial regulations are not consistently translated into actionable mechanisms across districts and municipalities. Prevention efforts, while present through child-friendly school initiatives and community campaigns, remain weakly institutionalised and vary significantly by locality. Intervention responses depend heavily on the operational strength of police units and child protection services, resulting in markedly stronger coordination in urban centres compared to rural areas. Rehabilitation constitutes the most structurally constrained pillar, evidenced by limited psychological services, insufficient safe houses, and the absence of standardised multi-sector protocols for long-term recovery. Overall, the study concludes that West Kalimantan’s response to child sexual violence remains reactive and only partially systemic, despite the existence of relevant regional regulations. Strengthening vertical policy integration, building sustained service capacity, and institutionalising cross-sector coordination are critical for ensuring a more equitable, comprehensive, and evidence-based child protection system across the province.